Parietaria cornuta (Urticaceae), a new species from the Anti-Atlas (Morocco), with a remarkable horned perianth - Chambouleyron, Mathieu; Léger, Jean-François; Charrier, Matthieu (Phytotaxa, 2025)
Parietaria cornuta, a new therophyte species, is described and illustrated from rocky habitats of the Anti-Atlas (Morocco). This species presents a highly original female perianth feature within the genus, with a horned base, whereas the other characters clearly refer to the genus (e.g., leaf shape and phyllotaxy, inflorescence in clusters of polygamous axillary flowers, female perianth free from the ovary, one achene per flower, achene shape). Its ecology, distribution, and conservation status are discussed.